(untitled) (CAHIERS MAGELLANES-NS, 2024)
Humans, as social beings, naturally tend to discuss their feelings and opinions with family members, friends, and colleagues. Investment decision-making is crucial; when grounded in proper fundamental and technical analysis, it can lead to profits. However, if influenced by herding behavior, it may result in unfavorable outcomes. Therefore, managing this behavioral tendency is essential to avoid losses caused by decisions that are not made independently. Financial literacy is also a critical factor for those who wish to analyze investment choices independently, understand basic financial terms, and effectively use financial products. Thus, it is important to study the impact of herding behavior on investment decision-making and the moderating role of financial literacy. This study explores how herding behavior influences investment decisions and how financial literacy acts as a moderating factor. Primary data were collected through structured questionnaires, which included 5-point Likert scale questions. The data comprises 209 responses, and descriptive statistics, correlation, and regression analyses were conducted using SPSS software. The study concludes that financial literacy moderates the effect of herding behavior on investment decision-making, with the impact of herding decreasing as financial literacy increases.